Characterization of calcium bentonite to use as a natural barrier in a surface repository (Brazilian Journal of Radiation Sciences (BJRS), 2022)
The wide use of nuclear technology in Brazil generates radioactive waste that, in general, have low and medium levels of radiation. This requires efficient management to keep the environment, humans and future generations safe. CNEN coordinates the CENTENA project which will consist of the implementation of the first national repository that will be a definitive solution for the storage of radioactive waste. It will be surface and multiple barriers, and bentonite will possibly compose the natural barrier, since it has good sorption capacity for several radionuclides and low hydraulic conductivity. This paper describes the practical work that followed the clay characterization protocol for use in a surface repository with calcium bentonite and proposes a future study to characterize the mixture of soil and bentonite with the addition of 8% and 15% clay in the soil in order to investigate what will be the best feasible combination to maintain the safety and economic viability of the project. XRD results confirmed the presence of montmorillonite, particle size analysis identified that 40% of the measured sample had an average particle size between 8.0 and 10.0 µm, the global average bentonite moisture was 14%, the high specific surface area value 82.741m2/g, the particle density value was 2.5287 ± 0.0057 g/cm³ and the result of the cation exchange capacity by the methylene blue adsorption method was 750 ± 18.71 mmol.kg-1. All these results indicated that calcium bentonite is a good natural material to be used in the Brazilian repository.